Metabolic derangements mediate cognitive impairment and Alzheimer's disease: role of peripheral insulin resistance diseases - de la Monte, Suzanne M. (Panminerva Med, 2012)
Herein, we review evidence that systemic insulin resistance diseases linked to obesity, type 2 diabetes, and non-alcoholic steatohepatitis promote neurodegeneration. Insulin resistance dysregulates lipid metabolism, which promotes ceramide accumulation with attendant inflammation and ER stress. Mechanistically, we propose that toxic ceramides generated in extra-CNS tissues, e.g. liver, get released into peripheral blood, and subsequently transit across the blood-brain barrier into the brain where they induce brain insulin resistance, inflammation, and cell death (extrinsic pathway). These abnormalities establish or help propagate a cascade of neurodegeneration associated with increased ER stress and ceramide generation, which exacerbate brain insulin resistance, cell death, myelin degeneration, and neuro-inflammation. The data suggest that a mal-signaling network mediated by toxic ceramides, ER stress, and insulin resistance should be targeted to disrupt positive feedback loops that drive the AD neurodegeneration cascade.